2006
DOI: 10.1111/j.1440-1746.2006.04199.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of cagA status and vacA subtypes of Helicobacter pylori in determining gastric histopathology: Virulence markers of H. pylori and histopathology

Abstract: The presence of the cagA gene is strongly associated with atrophic and active gastritis. Distinct vacA subtypes of H. pylori appear to have no association with histopathological findings of gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The results of some studies have shown that H. pylori CagA ? strains induce more severe mucosal damage and inflammatory responses [6,7]. Because CagA is immunodominant, serum IgG antibodies to the CagA antigen have been reported to be a reliable marker of carriage of a CagA ?…”
Section: Introductionmentioning
confidence: 99%
“…The results of some studies have shown that H. pylori CagA ? strains induce more severe mucosal damage and inflammatory responses [6,7]. Because CagA is immunodominant, serum IgG antibodies to the CagA antigen have been reported to be a reliable marker of carriage of a CagA ?…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are few data available as regards the pattern of H. pylori genotypes from Turkey [24–27] where the prevalence of GC is much lower than that in certain Asian countries [28]. All these studies [24–26] agreed with the importance of cagA in clinical outcome and histopathologic activity [27]; however, the importance of vacA subtypes has not been confirmed yet. Additionally, the clinical relevance of the H. pylori cagE , iceA , and babA2 genotypes has not been determined yet in clinical isolates from Turkey.…”
mentioning
confidence: 99%
“…Microorganisms associate with the mucin component MUC5CA and TFF1 protein, which stimulates the proteolytic activity of mucinase, increasing the fluidity of mucus. This mechanism facilitates the penetration of bacteria through the protective layer and determine the tropism of the bacteria to gastric epithelial cells [15]. In vitro studies have investigated the effect of mucin on the adhesion of H. pylori to glass surfaces.…”
Section: Factors Influencing Helicobacter Pylori Biofilm Formation Inmentioning
confidence: 99%
“…Movement, chemotaxis, adhesion processes conditioning secretion of adhesion molecules, as well as the ability to produce urease and VacA toxin, are the crucial skills conditioning the survival of H. pylori in the infection site [15]. The H. pylori cell wall contains lipopolysaccharide (LPS), which can induce a local and systemic inflammatory response in mammalian cells.…”
Section: Factors Influencing Helicobacter Pylori Biofilm Formation Inmentioning
confidence: 99%